Feature extraction for swiftlet sound attraction - Siti Nurzalikha Zaini, Husni Zaini; Kamarul Hawari, Ghazali; Saiful Nizam, Tajuddin (2013)
This research about the analysis of sound for swiftlets to enter the swiftlets house. There are important thing for industry to attract swiftlets enter and build their nests in man-made house. Swiftlet house use swiftlet voice call recording to attract attention bird go inside house to be doing nest. Therefore, this study analyze sound features that has attracted attention bird. By apply technique Mel-Frequency Cepstral Coefficient (MFCC) in speech processing on swiftlet sound. The sample of swiftlet voices are play on in swiftlet's house used to find the coefficient.